Ventricular-arterial coupling: changes with ageing and implications across cardiovascular conditions - Mateusz Gaczoł; Marek Rajzer; Wiktoria Wojciechowska (Blood Pressure)
Purpose Ventricular-arterial coupling (VAC) is a crucial concept in cardiovascular physiology, representing the dynamic interaction between the left ventricle and the arterial system. This comprehensive literature review explores the changes in VAC with ageing and various cardiovascular diseases (CVDs).Materials and methods This literature review covers studies on changes in VAC with age and common CVDs, such as arterial hypertension, atrial fibrillation (AF) and heart failure with preserved and reduced ejection fraction and aortic stenosis (AS). The review discusses traditional measures of VAC, including arterial elastance (Ea) and ventricular elastance (Ees), as well as emerging parameters, such as global longitudinal strain (GLS) and pulse wave velocity (PWV). The review introduces the PWV/GLS ratio as a novel method for assessing VAC.Results With ageing, both Ea and Ees increase, while the Ea/Ees ratio remains relatively stable, reflecting balanced arterial and ventricular adaptations. Novel measures, such as PWV/GLS ratio, show greater impairment in older adults and provide a comprehensive evaluation of VAC.Conclusions Ageing disrupts VAC through arterial stiffening and reduced heart function, often exacerbated by CVDs. Novel metrics like PWV/GLS may improve VAC assessment, helping clinicians manage age-related cardiovascular issues by identifying risks earlier and guiding treatment to support efficient heart–artery interaction.